2018
DOI: 10.1097/adm.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Pregnancy Treatment Interventions for Moms (OPTI-Mom): A Pilot Study

Abstract: These findings provide support that PN is a feasible adjunctive intervention that shows promise for health improvements and service engagement among treatment-seeking pregnant women with opioid dependence initiating buprenorphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…9,31,32,40 -43 We examined an increase in different treatment modalities, but most programs strived to be convenient, 5,44 practical, 12,31 and emotionally supportive. 13,31,32 The attention to enhanced convenience was evident in multiple treatment interventions: these program components included child care options, 45 parenting education sessions, 29 case management, 43 and treatment coordination. 19,32,40 The treatment programs attended to the social and psychosocial needs of mothers by focusing on self-sufficiency, 41 integrating family involvement and support, 6 teaching parenting techniques, 29,31,41 providing a linkage to social service agencies, 12 and offering vocational education.…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…9,31,32,40 -43 We examined an increase in different treatment modalities, but most programs strived to be convenient, 5,44 practical, 12,31 and emotionally supportive. 13,31,32 The attention to enhanced convenience was evident in multiple treatment interventions: these program components included child care options, 45 parenting education sessions, 29 case management, 43 and treatment coordination. 19,32,40 The treatment programs attended to the social and psychosocial needs of mothers by focusing on self-sufficiency, 41 integrating family involvement and support, 6 teaching parenting techniques, 29,31,41 providing a linkage to social service agencies, 12 and offering vocational education.…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…However, PN has only recently begun to be researched in relation to behavioral health problems [29,[54][55][56], such as smoking cessation improvements [57], HIV management [58] and our team's proof-of-concept study that demonstrated intervention feasibility among pregnant women with OUD. Specifically, our proof-of-concept study findings demonstrated promising initial results for women in a number of behavioral and physical health domains, including improvements in opioid/substance use, mental health, and prenatal care outcomes [20]. This multisite pilot trial study expands upon this previous PN intervention to further establish the internal and external validity of these findings and the potential value of the PN intervention for pregnant women with OUD.…”
Section: Discussionmentioning
confidence: 64%
“…This study is testing a PN intervention for pregnant women with OUD and assessing linkage/retention in care. Importantly, this study builds upon a proof-of-concept project among 21 pregnant women with who were provided the PN intervention that utilized a one-group repeated measures design [20].…”
Section: Introductionmentioning
confidence: 99%
“…Parents with OUD have been shown to avoid care as a result of guilt, shame, embarrassment, fear of judgment from health care providers, criminalization, and loss of custody of their children 7,8 . Health care workers, including midwives, should approach individuals and families experiencing OUD with compassion, understanding, and the use of a comprehensive care model consisting of medication‐assisted therapy (MAT), 9 concomitant psychiatric care, 10,11 and a focus on progression rather than complete substance abstinence. The use of such a model has been shown to improve maternal and infant outcomes 8,9,12 .…”
Section: Introductionmentioning
confidence: 99%